2021
DOI: 10.2166/aqua.2021.187
|View full text |Cite
|
Sign up to set email alerts
|

Efficiencies of indigenous South African plant biofilters for urban stormwater runoff water quality improvement with a focus on nutrients and metals

Abstract: In South Africa, urban activities contribute high levels of pollution to rivers and groundwater via stormwater runoff. In reducing urban stormwater loads of engineered plant biofiltration, an effective and self-sustaining component of green infrastructure is a treatment option. The country's extensive natural biodiversity offers untapped potential of indigenous species' use in plant biofilters. This paper presents the findings of a plant biofilter column experiment, which investigated the performance of nine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…Likewise C. textilis performed well relative to results of a review of eight studies, conducted mainly in China, which found that phosphorus uptake rates for numerous plant species, including Canna indica, P. australis, J. effusus and Typha species, varied between 2 and 163 mgP.m − 2 .d − 1 (Wang et al, 2020). A study conducted after ours, investigating the use of nine South African endemic plant species for use in bio lters, also con rmed that C. textilis and P. serratum consistently showed some of the best results in terms of nutrient removal relative to the other seven species (Jacklin et al, 2021b).…”
Section: Nutrient Uptake Potentialsupporting
confidence: 56%
See 1 more Smart Citation
“…Likewise C. textilis performed well relative to results of a review of eight studies, conducted mainly in China, which found that phosphorus uptake rates for numerous plant species, including Canna indica, P. australis, J. effusus and Typha species, varied between 2 and 163 mgP.m − 2 .d − 1 (Wang et al, 2020). A study conducted after ours, investigating the use of nine South African endemic plant species for use in bio lters, also con rmed that C. textilis and P. serratum consistently showed some of the best results in terms of nutrient removal relative to the other seven species (Jacklin et al, 2021b).…”
Section: Nutrient Uptake Potentialsupporting
confidence: 56%
“…Due to increasing demand for wastewater treatment, there is a need for more innovative, affordable and sustainable decentralised technologies to treat wastewater -particularly for developing nations (Kivaisi, 2001). Extensive research into design considerations and optimization has resulted in various types of constructed wetlands being developed for different wastewater types (Babatunde et al, 2008;Batchelor and Loots, 1997;Jacklin et al, 2021b;Wood and Pybus, 1992;Wu et al, 2015; S. Yeh et al, 2015). Floating wetlands, a type of constructed wetland, are manufactured buoyant structures designed to support emergent wetland plants.…”
Section: Introductionmentioning
confidence: 99%